Optimization of Conservative Treatment of Periodontal Diseases Using Modern Technologies (Eurasian Research Bulletin, 2023)
The aim of our study was to increase the effectiveness of treatment of patients with chronic generalized catarrhal gingivitis using dynamic electro neurostimulation and magnetotherapy techniques at the stage of conservative treatment.